Molecular insight into the micro-behaviors of CH4 and CO2 in montmorillonite slit-nanopores. Issue 13 (2nd November 2017) - Sun, Haoyang; Zhao, Hui; Qi, Na; Qi, Xiaoqing; Zhang, Kai; Li, Ying
Abstract: The Grand Canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulation methods were used to investigate the adsorption and diffusion properties of CH4 and CO2 in montmorillonite slit-nanopores. It is found that, both CH4 and CO2 could adsorb closely onto the pore surface, while different adsorption states occur for CH4 and CO2, respectively, in montmorillonite slit-nanopores. Competitive adsorption of CO2 over CH4 exists in montmorillonite slit-nanopores, especially at the lower pressures, which is attributed to the different interaction intensity between the CH4 –CO2 molecules and the pore surface. The diffusion coefficients of CH4 and CO2 both decrease with the enhanced pressures, while the CO2 has a relative weak diffusion coefficient comparing with CH4 . A well displacement of the residual CH4 by CO2 in montmorillonite slit-nanopores was investigated, which is found that the displacement efficiency increases with the enhanced bulk pressures. It was determined that, the CO2 can be captured and reserved in the montmorillonite slit-nanopores during the displacement, and the sequestration amount of CO2 gets enhanced with the bulk pressure increasing. This study provides micro-behaviours of CH4 and CO2 in montmorillonite slit-nanopores, for the purpose to give out useful guidance for enhancing shale gas extraction by injecting CO2 .